O significado da anemia nos animais - Côdo, Vitório (Revista Ceres, 1954)
The author describes the meaning of anemia, the disturbances arising in domestic animals due to a reduction in the normal number of red corpuscles and amount of hemoglobin in the blood. He mentions a group of diseases which cause redution of the number of red corpuscles and also the influence of heredity on anemia. He describes the technique and precautions to be observed in blood transfusion, the determination of blood groups for transfusions to the horse and gives general direction on the amount of blood to be transfused.